Lung Nodule Detection Methods - Abhinao A, Somnathe; Devendra G, Ingale (International Journal of Computer Sciences and Engineering, 2025)
Lung nodules are small masses in the human lung and are usually spherical however they can be distorted by surrounding anatomical structures such as vessels and adjacent pleura. There are different methods evolved for the detection of lung nodules. In this paper, different techniques that are used for the detection of lung nodules are introduced.